Influence of the VEGF-A 936C>T germinal polymorphism on tumoral VEGF expression in head and neck cancer. (August 2009) - Formento, Jean-Louis; Etienne-Grimaldi, Marie-Christine; Francoual, Mireille; Pagèès, Gilles; Onesto, Cercina; Formento, Patricia; Chamorey, Emmanuel; Dassonville, Olivier; Poissonnet, Gilles; Milano, Géérard
Aims: Elevated tumoral vascular endothelial growth factor A (VEGF-A) expression is linked to poor survival in head and neck cancer patients. The aim of the present study was to analyze the influence of VEGF-A gene polymorphisms on tumoral VEGF-A expression and to test their prognostic value in head and neck cancer patients.Materials & methods: VEGF-A polymorphisms at position -2578C>A, -1498T>C, -1154G>A, -634G>C and 936C>T were analyzed (PCR-RFLP) in tumoral DNA, along with tumoral VEGF-A expression (ELISA), in 49 Caucasian head and neck cancer patients.Results: A trend towards a difference in tumoral VEGF-A expression depending on 936C>T polymorphism was observed, with a median at 540 pg/mg prot in CT + TT patients (n = 5) versus 940 pg/mg prot in CC patients (n = 44) (p = 0.064). VEGF-A expression was not related to any other polymorphism. Unlike tumoral VEGF-A expression, the analyzed genotypes were not related to patient survival.Conclusion: As opposed to tumoral VEGF-A expression, VEGF-A gene polymorphisms are not of prognostic value in head and neck cancer patients. Further studies aimed at confirming the influence of VEGF-A 936C>T germinal polymorphism on tumoral VEGF-A expression are needed.